Study Of Vacation Motives Among Various Groups Of People And Their Travel Intention - CHIN, SZU SZU (2005)
Tourism is an intangible industry. It is produced and consumed at the time and on site in which its marketing approach would be very much different as compared to other products which are tangible. Tourism destination marketing can be only effective when the tourism marketers understand the insight desires of each and everyone, particularly on what stimulate them to travel.